Resonant photocurrent from a single quantum emitter in tungsten diselenide. (18th August 2020) - Paur, Matthias; Molina-Mendoza, Aday J; Polyushkin, Dmitry; Michaelis de Vasconcellos, Steffen; Bratschitsch, Rudolf; Mueller, Thomas
Abstract: Single quantum emitters (SQEs) are the basic building blocks for quantum optics and quantum information technology. Strain-induced defects in monolayer transition metal dichalcogenides (TMDs) have been shown to be a promising platform for the generation of SQEs. In particular, achieving optically active and electrically controlled quantum emitters make these materials attractive for applications ranging from quantum communication and optoelectronics to high resolution metrology. Here, we report the spectral photoresponse of monolayer WSe2 upon strain, where we observe a connection between single-photon emission and photocurrent (PC) generation in a p-n device. A strong antibunching in second-order correlation from this localized emitter unambiguously demonstrates the single-photon nature of the emission, whereas the PC is highly dominated by the absorption at such a localized state, showing an exponential dependence with the applied electric field. Furthermore, we can resolve narrow PC peaks with 1.0 meV spectral width.